PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE THIK TALK WRITE (TTW) TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 2 LENGAYANG KABUPATEN PESISIR SELATAN - Rianti, Lili Vera; Zulfaneti, Zulfaneti; Yunita, Alfi (Pendidikan Matematika, 2014)
AbstrakÂ The background of the research is the lack of understanding mathematical concepts studentâs in learning mathematic. The aims of this research is to know the studentâs understanding of mathematical concepts by implementing cooperative learning model TTW is better than the studentâs understanding of mathematical concepts with conventional learning. Besign of this research is experimental research by random design. The population of research was students of class VIII grade SMP 2 Lengayang Academic Year 2013/2014, which consists of eight classes. Technique of random sampling , the sample is selected as class VIIId as experimental class and VIIIe as control class. Instrumentation of this research is the understanding of mathematical concepts Form of the test used is a form of essays with a reliability test is = 0.81. The technique data analysis is the one parties of t-test. Based on the calculation of the data analysis the class was normally distributed withÂ  = 0.0872Â  and = 0.1108. Hypothesis testing results obtained Â then the hypothesis in this research was received. It can be concluded that the studentâs understanding of mathematical concepts by implementing cooperative learning TTW is better than understanding ofÂ  mathematical concepts that students applying convensional learning in VIIIÂ  SMPN 2 Lengayang 2013/2014.